Does European integration make exports more complex? - Serwach, Tomasz; Gabrielczak, Piotr (Publishing House of Wroclaw University of Economics and Business, 2021)
The authors studied the determinants of export complexity aiming at an assessment of the impact of European integration on increased sophistication of exported goods. It is possible that EU membership leads to higher export complexity due to the emergence of new (advanced- technology-oriented) comparative advantages and inflow of capital, for instance, in the form of FDI. At the same time, countries without the supply conditions necessary to produce sophisticated products, may specialize in goods that are less complex. Such a theoretical ambiguity leads to the need to empirically assess the importance of EU accession for export complexity. The study applied panel data analysis. The results indicate that the European Union may have increased the complexity in member states’ exports, especially in the less advanced economies
Argumenta Oeconomica, 2021, Nr 1 (46), s. 155-168